Making states work : state failure and the crisis of governance - Chesterman, Simon; Ignatieff, Michael; Thakur, Ramesh, 1948- (United Nations University Press, 2005)
In the wealth of literature on state failure, surprisingly little attention has been paid to the question of what constitutes state success and what enables a state to succeed. This book is a joint project of the International Peace Academy and the United Nations University and examines the strategies and tactics of international actors, local political elites, and civil society groups to build or rebuild public institutions before they reach the point of failure: to make the state work. It is frequently assumed that the collapse of state structures, whether through defeat by an exter-nal power.